2015
DOI: 10.1038/bonekey.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress, sympathetic activation and skeletal metastasis of breast cancer cells

Abstract: Improved detection programs and new therapies significantly improved the 5-year survival rate of women with breast cancer. However, some women still relapse and succumb to cancer because of metastatic disease. In particular, chronically depressed patients do not seem to benefit from newly developed treatments and present with shorter survival. The reason for this association is unclear, but recent cues from preclinical studies point to the possible contribution of neuroendocrine factors generated in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Contrastingly, the use of β‐blockers as adjuvant therapy in patients diagnosed with breast cancer may have several therapeutic advantages. If both Vegf‐a and Rankl are β2AR target genes and critical mediators of bone resorption, angiogenesis, and metastatic cancer cell colonization of bone, the use of a single drug with β‐blockade activity has the potential of reducing bone resorption, angiogenesis, and bone tumor establishment in at‐risk patients . These properties could make β‐blockers particularly efficacious in preventing disseminated cancer cells from reaching the safe heaven of the bone microenvironment and may expose these cells more readily to chemotherapy or actions of the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrastingly, the use of β‐blockers as adjuvant therapy in patients diagnosed with breast cancer may have several therapeutic advantages. If both Vegf‐a and Rankl are β2AR target genes and critical mediators of bone resorption, angiogenesis, and metastatic cancer cell colonization of bone, the use of a single drug with β‐blockade activity has the potential of reducing bone resorption, angiogenesis, and bone tumor establishment in at‐risk patients . These properties could make β‐blockers particularly efficacious in preventing disseminated cancer cells from reaching the safe heaven of the bone microenvironment and may expose these cells more readily to chemotherapy or actions of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…If both Vegf-a and Rankl are b2AR target genes and critical mediators of bone resorption, angiogenesis, and metastatic cancer cell colonization of bone, the use of a single drug with b-blockade activity has the potential of reducing bone resorption, angiogenesis, and bone tumor establishment in at-risk patients. (52) These properties could make b-blockers particularly efficacious in preventing disseminated cancer cells from reaching the safe heaven of the bone microenvironment and may expose these cells more readily to chemotherapy or actions of the immune system. In that regard, several preclinical and clinical studies have shown a benefit from b-blocker use on survival in patients with triple negative breast cancer, non-small cell lung cancer, hemangiomas, and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Restraint stress facilitates cancer angiogenesis and metastasis by releasing β-END, prolactin, increasing concentrations of circulating catecholamine and GC, and increasing tumor-associated macrophage infiltration into the primary tumor (37,38). Psychological stress may attenuate antiangiogenic therapy, primarily through activating β-adrenergic signaling to promote tumor angiogenesis (39), and β-blockers or behavioral therapies can limit skeletal metastasis of breast cancer cells (40). Dopamine (DA) is also a catecholamine hormone, which can stabilize tumor blood vessels to block the effects of chronic stress on tumor vasculature, as the depletion of DA under chronic stress conditions creates a permissive microenvironment for tumor growth (41,42).…”
Section: Mechanisms Underlying the Effects Of Stress On Tumorigenesismentioning
confidence: 99%
“…The sympathetic nervous system regulates the organism's vital involuntary functions and is in charge of the "fight-or-flight" response in danger and stressful situations and modulates the connection between the central nervous system and immune system [13].…”
Section: Sympathetic Nervous Systemmentioning
confidence: 99%
“…Epinephrine arrives to the target tissue through blood circulation after being produced in the adrenal gland. Both norepinephrine and epinephrine bind with different affinities to adrenergic receptors α (α 1 /α 2 ) and β (β 1 /β 2 /β 3 ) in target cells in different tissues and organs, such as the heart, brain, adipose tissue, mammary gland, ovaries, prostate, lymphoid tissue, bones, and different types of cancer cells [13,14].…”
Section: Sympathetic Nervous Systemmentioning
confidence: 99%